MASA DEPAN ENERGI DAN EKONOMI: SEBUAH KAJIAN KONSUMSI ENERGI DI INDONESIA - Iyan, Yanuar Bangun Nurcahyo; Sukarso2, Aso; Jumri3 (Bina Ekonomi, 2025)
This research depends on the understanding of the role of energy in economic development, emphasizing its classification as a resource or, more succinctly, as a form of capital in the production sector. The study focuses on the Indonesian economy from 1990 to 2022, aiming to comprehensively analyze the relationship and impact of both non-renewable and renewable energy sources on the economy. The analytical methodology employed in this research includes Granger causality tests and the Error Correction Model (ECM) to unveil the contribution of energy to the economy. The research findings explicate that the relationship originates from the energy sector, subsequently influencing the economy. Currently, non-renewable energy continues to play a crucial role in economic development, based on various implications of ongoing plans, regulations, and policies. However, this does not preclude the possibility that renewable energy will assume a pivotal role in the future.